Writing the classroom: pedagogical documents as rhetorical genres - Neaderhiser, Stephen E., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2022)
Writing the Classroom explores faculty's use of pedagogical documents to establish classroom expectations and schedules as well as articulate professional identities performed by faculty teachers inside and outside the classroom, arguing that genres like prompts, proposals, statements, and policy documents are fundamental in constructing the broader pedagogical enterprise within academia.--Provided by publisher.
The syllabus: a gateway to or gatekeeper of the profession / Michael Albright -- Feminist writing assignments: enacting pedagogy through classroom genres / Kate Navickas -- Patterns, negotiations, and ideologies: contract grading as genre / Virginia M. Schwarz -- Evaluative feedback genres: sites for exploring writing teacher development / Jessica Rivera-Mueller -- Occlusion in a classroom genre set: assessing assignment sheets and grading rubrics / Dustin Morris and Lindsay Clark -- "But nobody looks at these!": making the rhetorical case for syllabi of record / Amy Ferdinandt Stolley and Christopher Toth -- "Is it in the handbook?": the role of departmental teaching handbooks in developing pedagogical identity / Dana Comi -- "Am I covered for that?": examining the "work" of policy documents in the first-year course / Mark A. Hannah and Christina Saidy -- Recommendation, requirement, and reproduction: sanctioned uptake in classroom accessibility statements / Matt Dowell -- Written in homely discourse: a case study of intellectual and institutional identity in teaching genres / Megan Schoen, Jim Nugent, Cindy Mooty, and Lori Ostergaard -- Performing reflection in institutional contexts: a genre approach to compelled reflective writing / Lesley Erin Bartlett -- Genre anxiety: the pedagogical, political, and emotional work of making a certificate / Laura R. Micciche and Lora Arduser -- Pedagogical identity in a digital world: challenge and collaboration in the course proposal genre / Cynthia Pengilly -- Toward the learning to teach statement / Megan Knight and Kate Nesbit -- COGs in the pedagogical machine: the structuration, rhetorical situations, and perigenres surrounding classroom observation guidelines / Zack K. De Piero -- Outcomes statements as meta-genres: the (transformative) role of outcomes statements in program revision / Logan Bearden.
Keywords: Education, Higher -- Curricula; College teaching; English language -- Rhetoric -- Study and teaching (Higher); Literary form -- Study and teaching (Higher)